2011
DOI: 10.1080/02755947.2011.571490
|View full text |Cite
|
Sign up to set email alerts
|

Winter Catch‐and‐Release Hooking Mortality of Saugers below Lock and Dam 3 of the Mississippi River

Abstract: We evaluated the effect of length and depth of capture of saugers Sander canadensis on winter hooking mortality below Lock and Dam 3 of the Mississippi River (i.e., Pool 4) by catching saugers using the most common recreational fishing gear in these fisheries (jig and plastic, jig and minnow, and jigging spoons) and holding the fish for 72 h in a net-pen. Sauger winter hooking mortality was 26.4% and increased with depth of capture. Thirty-three percent (56 of 172) of the saugers caught at depths of 9 to 24 m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Schreer et al (2009) reported that walleyes and yellow perch caught at greater depths were more likely to have barotrauma and die as a result of it. Meerbeek and Hoxmeier (2011), who observed a hooking mortality rate (26%) similar to our estimates (22-32%), also reported a direct relationship between mortality and capture depth for the saugers they angled in the upper Mississippi River at depths down to 24 m. Finally, Schramm et al (2010) also concluded that capture depth in tournaments inversely affected the survival of walleyes and saugers (although warm temperatures were considered to be the primary determinant of mortality in released fish). However, no such statistical relationships between fate and the incidence of gastric distension or depth of capture revealed themselves to us in the results presented herein.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Schreer et al (2009) reported that walleyes and yellow perch caught at greater depths were more likely to have barotrauma and die as a result of it. Meerbeek and Hoxmeier (2011), who observed a hooking mortality rate (26%) similar to our estimates (22-32%), also reported a direct relationship between mortality and capture depth for the saugers they angled in the upper Mississippi River at depths down to 24 m. Finally, Schramm et al (2010) also concluded that capture depth in tournaments inversely affected the survival of walleyes and saugers (although warm temperatures were considered to be the primary determinant of mortality in released fish). However, no such statistical relationships between fate and the incidence of gastric distension or depth of capture revealed themselves to us in the results presented herein.…”
Section: Discussionsupporting
confidence: 85%
“…Although Patterson et al (2000) and Stewart (2007) reported that large red snappers and silver seabreams Pagrus auratus were more likely to survive than small ones, length was not a significant predictor of hooking mortality for West Australian dhufish Glaucosoma hebraicu (Gitschlag and Renaud 1994). Similarly, Meerbeek and Hoxmeier (2011) detected no relationship between sauger lengths and survival, and Schreer et al (2009) found no relationship between the sizes of walleye and yellow perch Perca flavescens and the incidence of barotrauma or survival. Bettoli et al (2000) suspected that ascent rate is an important factor in determining the incidence of barotrauma (and possibly survival) in saugers; however, ascent rate was not statistically related to survival in the present study.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Bruesewitz et al (1993) found low mortality rates (<10%) during winter months characterized by very cold water temperatures. In contrast, Meerbeek and Hoxmeier (2011) found hooking mortality rates of 26.4% for saugers S. canadensis angled from the Mississippi River during winter months. Although both of these studies addressed water depth, neither addressed open-water angling during normal summer temperatures.…”
Section: Discussionmentioning
confidence: 98%
“…Bruesewitz et al (1993) found low mortality rates (<10%) during winter months characterized by very cold water temperatures. In contrast, Meerbeek and Hoxmeier (2011) Angling at great depths has the potential to have critical physiological impacts on released fish, especially physoclistous species. Feathers and Knable (1983) found that bloating and external hemorrhaging occurred in largemouth bass Micropterus salmoides that were caught from depths of 18-27 m. Impacts, albeit less significant, also occurred at shallower depths.…”
Section: Discussionmentioning
confidence: 99%